Polish-English LSP Dictionaries in Translation Work: Labour-Law Terminology from the Polish Labour Code in Terminographic and Translation Practice - Agnieszka Rzepkowska (Language, Culture, Politics)
The purpose of the article is to show the applicability of selected Polish-English LSP dictionaries in legal translation work. The paper analyses how well labour-law terminology, found in the Polish Labour Code, is covered in Polish-English LSP dictionaries and compares them to equivalents selected by Agnieszka Jamroży, the author of an English translation of the Polish Labour Code. Based on a collation of the English equivalents present in the reviewed resources, the author presents some conclusions as to what the studied dictionaries lack and what terminographers should focus on when compiling a labour-law dictionary that would be more useful to translators and other users. Essentially, the article presents the Polish labour-law language system and labour-law corpus, legal terms and labour law in the context of LSP dictionaries. The methodology is then outlined, followed by the findings from the review of the selected dictionaries and an example translation of the Polish Labour Code. Certain labour-law terms particularly stood out, and these have been reviewed in detail in the paper: they are documentacja pracownicza, wymiar czasu pracy, norma czasu pracy and dobowy wymiar czasu pracy. The publication ends with conclusions and findings on the applicability of Polish-English LSP dictionaries in legal translation work and implications for creating a labour-law dictionary for translation purposes based on the research.